Tomato-induced occupational asthma in a greenhouse worker - Vandenplas, Olivier; Sohy, Carine; D'Alpaos, Vinciane; Nootens, Carine; Thimpont, Joël; Weigand, Daniela; Scheurer, Stephan (Journal of allergy and clinical immunology, 2008)
To the Editor: Tomatoes (Lycopersicum esculentum, botanical family of Solanaceae) are a well-documented source of IgE-mediated food allergy,1 but only 1 report has suggested the possibility of an occupational respiratory allergy to tomato allergens.2 Herein we report the clinical and immunologic findings in a tomato greenhouse worker who had occupational asthma and rhinitis. The subject's serum exhibited specific IgE antibodies against tomato (7.3 IU/mL) and other plants belonging to the Solanaceae family, including potato (3.1 IU/mL), sweet bell pepper (2.1 IU/mL), eggplant (2.4 IU/mL), and chili pepper (1.9 IU/mL), as well as against natural rubber latex (2.7 IU/mL), mugwort (1.5 IU/mL), timothy grass (3.1 IU/mL), birch (2.8 IU/mL), and recombinant Bet v 1 (1.6 U/mL; ImmunoCAP method; Phadia Diagnostics, Uppsala, Sweden).